The Impact of Electrical Energy Consumption on the Payback Period of a Rooftop Grid-Connected Photovoltaic System: A case Study from Vietnam - Ngo, Xuan Cuong; Do, Nhu Y (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Recently, the use of small-scale grid-connected photovoltaic (GCPV) systems for households has been growing in Vietnam. The installation of a rooftop GCPV system provides many benefits to households, such as lowering monthly electricity bills, reducing absorbed heat of the building, and creating additional income by penetrating electric power to the grid. However, the technical issues of the payback period is complicated and requires a lot of considerations. The main goal of this study is to develop a computational model and investigate the effect of electrical energy consumption on the payback period of rooftop GCPV systems. A case study is used in this study to create a model of a rooftop GCPV system for households in north-central Vietnam under feed-in tariff (FiT) schemes. The results show that the investment rate and electrical energy consumption of the installed household have a strong influence on the payback period of the GCPV system. In the case of the lowest investment rate of 666.4 USD/kWp, the fastest payback period is 43 months for households consuming all of the generating energy of the GCPV system, and the longest payback period is 131 months for households that do not use electricity, implying that all of the generating energy of the GCPV system is connected and sold to the distribution grid. The research findings will actively assist in calculating the installed capacity suitable for households in order to have the most suitable payback period while also assisting policymakers in the future in setting a reasonable rate of feed-in tariff for rooftop GCPV systems